ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK MAHASISWA PADA PEMBELAJARAN PROBLEM BASED LEARNING DITINJAU DARI GAYA BELAJAR - Kusuma, Adi Candra; Azhar, Gillang Al; Rifai, Muhamad; Ekasari, Silvia Rahmi (Universitas Bhinneka PGRI, 2024)
The purpose of this study is to describe students' mathematical communication skills in Problem Based Learning viewed from students' learning styles. The type of research used is qualitative research supported by observation data, questionnaires and interviews. Validity testing is the credibility test, transferability, dependability, and confirmability. The results of the study indicate that students' mathematical communication skills viewed from learning styles include visual learning styles (30.4%), auditory (34.8%), and kinesthetic (26.1%) and visual-kinesthetic (8.7%). Mathematical ability indicators on a scale of 0-10 include 1) The ability to express ideas orally, in writing and demonstrate them and describe them visually (8.78), 2) The ability to understand, interpret, and evaluate mathematical ideas orally, in writing and demonstrate them and describe them visually (8.21), 3) The ability to use mathematical terms, notations, and their structures to present ideas describing relationships with situation models (5.30). The appropriate learning style is the key to student success in learning. The use of learning styles that are limited to only one form can cause an imbalance in absorbing information. Therefore, in learning activities, students need to be helped and directed to recognize the learning style that suits them so that learning objectives can be achieved effectively.